Steel H-Section Piles Support 2,120-Foot Long Cable Stayed Bridge Verona Island And Prospect, Maine - James W. Weaver (Deep Foundations Institute, 2011)
The 2,120-foot long cable stayed Penobscot Narrows Bridge that carries US Route 1 over the Penobscot River between Verona Island and Prospect, Maine is supported on four foundation units, one below each pylon and one at each abutment. Due to varying subsurface conditions along the bridge alignment, the structure was designed to be supported on foundations consisting of high-capacity steel H-section piles (Verona Pylon), a mat bearing on a prepared bedrock surface (Prospect Pylon) and spread footings bearing on compacted rockfill (abutments). The 70-foot by 80-foot (plan area) Verona Pylon foundation was designed to be supported by 288, 430-kip design capacity steel H-section piles (HP14x117, 50 ksi steel) driven through up to 100 feet of dense glacial till deposits containing cobbles and boulders up to 3 feet in diameter. The piles were installed using a single-acting diesel hammer (Delmag D62-22) with a maximum rated energy of 165 kip-ft. Thirteen representative piles were selected for dynamic testing (ASTM D-4945) to verify pile capacity, hammer efficiency and pile stresses. Dynamic testing determined that four different pile driving criteria were needed across the site due to variation in the bedrock and soil resistance below the footing plan area. Approximately 4 percent of the production piles were damaged/rejected due to misalignment and/or damage as a result of encountering the cobbles and boulders embedded in the glacial till. The rejected piles were located randomly throughout the plan limits of the foundation mat. Subsequent structural analyses indicated that the foundation was capable of safely supporting the design loads without the need for installing replacement piles. Evaluation of dynamic testing results with signal matching and pile driving records provided valuable information on pile side and tip resistance. Evaluations were made regarding predicted versus actual pile lengths, pile bearing material, distribution of skin friction and end bearing capacities.